Competency Management and Green Economy Education in the Field of Civil Engineering: A Traffic Project Based Approach - Aldi Adi Pratama; Tgk Harmen Nuriqmar; Maria Theodora; Bintoro Ariyanto; Rakha Ramadhana (Universitas Negeri Yogyakarta, 2024)
Background: the modern era is characterized by the acceleration of infrastructure development and the increasing need for efficient transportation. Civil engineering human resource planning plays an important role in ensuring the availability of a workforce that has the required skills and knowledge. This article aims to explore the relationship between these three elements and how their application can contribute to achieving more efficient, environmentally friendly and sustainable traffic projects. Methods: The method used in this research uses qualitative and quantitative methods. The qualitative method only prioritizes literature studies by collecting competency and green economy keywords from trusted journal literature. Meanwhile, the quantitative method used is analysis and processing of project data and case studies of sustainable traffic projects, supported by questionnaire data. Results: 40% of civil engineering companies have in-depth knowledge of environmental regulations that apply in Indonesia. Cities like Jakarta are still lagging behind in implementing smart traffic systems. Of the 100 major cities in the world, Jakarta ranks 85th in terms of adoption of smart traffic technology, with implementation still below 20%. 30% of civil engineering professionals in Indonesia report strong collaboration between civil engineers, environmental experts and urban planners. Green projects in Indonesia have only reached USD 15 billion of the need of around USD 500 billion to achieve the national emission reduction target by 2030. 23% of infrastructure projects in Indonesia use environmentally friendly technology in their construction phase. This shows the low adoption of green technology in civil infrastructure. Conclusion: The government can promote more green technology projects, such as implementing Leadership in Energy and Environmental Design (LEED) standards or the Green Building Council Indonesia and encouraging cross-disciplinary projects by forming teams consisting of various experts, including environmental experts, transportation planners, and engineers, from the planning stage to implementation. While increasing understanding of green financing through seminars, workshops and training in the civil engineering sector, as well as encouraging easier access to green financing schemes from local and international financial institutions